Reinstatement of Aloe verdoorniae (Asphodelaceae subfam. Alooideae), a distinctively purplish blue-leaved species of maculate aloe endemic to the eastern Gauteng and western Mpumalanga provinces of South Africa - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2023)
Aloe verdoorniae (Asphodelaceae subfam. Alooideae), which generally has been included in the synonymy of A. greatheadii var. davyana since 1987, is formally reinstated as an accepted species that is endemic to the eastern Gauteng and western and central Mpumalanga provinces of South Africa. Aloe davyana itself was recently reinstated at the rank of species. Aloe verdoorniae differs from A. davyana in several vegetative and reproductive morphological characters so warranting its recognition at the rank of species; the differences are quantified and discussed. The typification of the name A. verdoorniae is reinterpreted and corrected. The species is illustrated and an amplified description is provided for it.